KOMUNITAS RAYAP TANAH DI SEPULUH LOKASI DI DKI JAKARTA - Ginuk Sumarni; Agus lsmanto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Subterranean termites are important insects which attack structural timber. Six species have been found at ten locations of the Jakarta Metropolitan: Microtermes insperatus, M. incertoides, Odontotermes javanicus, Macrotermes gilvus, Schedorhinotermes javanicus, and Coptotermes curvignathus. Various termite species prevail in two of the locations (P. Rebo and P. Minggu). M. insperatus was found to be the largest population in every location. Cempaka Putih was the lowest in similarity and diversity indexes of the termite species. The same termite species was found in Kramat Jati and Kebayoran Baru. No subterranean termites were found in Cilincing, Tanjung Priok, and Kemayoran